Memory Development from Early Childhood Through Emerging Adulthood - Schneider, Wolfgang (Springer International Publishing : Imprint: Springer, 2015)
Memory is intimately involved with higher cognitive functions such as decision making and problem solving. It is front and center even in the most basic workings of the human mind. These multiple connections make memory a more diversified entity than we once thought it to be. But how does this all evolve in the individual, and over how long a time?  Memory Development from Early Childhood Through Emerging Adulthood reviews current insights into ongoing and newer areas of developmental memory studies as well as innovations in testing, experimental design, and modeling. Chapters focus on pre-verbal and verbal memory, visuospatial memory, encoding and retrieval strategies, metamemory, and other core elements, locating their emergence from early infancy through emerging adulthood. The book's range of theories and findings carries considerable implications for study areas as varied as brain-behavior connections, children's learning styles, and the effects of early experiences on the developing psyche.  Key topics addressed include: The development of implicit memory Memory development during the infant and toddler years The development of event and autobiographical memory in childhood and adolescence The role of basic memory capacity and working memory Effects of the knowledge base on memory development The development of metamemory  Memory Development from Early Childhood Through Emerging Adulthood is an essential resource for researchers, graduate students, and clinicians/scientist-practitioners in developmental and cognitive psychology as well as related mental and educational disciplines.  .